2020
DOI: 10.31557/apjcc.2020.5.3.157-160
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Oral Sub Mucous Fibrosis and Its Correlation with the Level of Education in Patients Coming to a Tertiary Care Hospital of Karachi from January 2018 to December 2018

Abstract: Objective: To determine the frequency of oral submucous fibrosis in patients coming to dental OPD of a tertiary care hospital and to correlate the association of level of education among patients of oral submucous fibrosis.Methodology: A cross sectional study was conducted from January 2018 to December 2018 among patients coming to the dental OPD of a tertiary care hospital in Karachi. Convenience sampling was used to select patients of Oral Submucous Fibrosis and a structured questionnaire was used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…In the present study, there were 59.04% males and 40.96% females with male to female ratio being 1.4:1 which is similar to findings of Tariq et al 17 , Hosein et al 19 , and Memon et al 21 conducted in Pakistan. However, these findings are inconsistent with recent literature in India as reported by Saalim et al 18 and Gondivkar et al 22 , where male to female ratio was 6.4:1 and 7.5:1 respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, there were 59.04% males and 40.96% females with male to female ratio being 1.4:1 which is similar to findings of Tariq et al 17 , Hosein et al 19 , and Memon et al 21 conducted in Pakistan. However, these findings are inconsistent with recent literature in India as reported by Saalim et al 18 and Gondivkar et al 22 , where male to female ratio was 6.4:1 and 7.5:1 respectively.…”
Section: Discussionsupporting
confidence: 90%
“…As far as role of education with use of areca nut and tobacco is concerned, 53% of OSMF patients presenting with history of risk habits were uneducated or had primary education while 38% had higher secondary education and 8.4% patients were graduate. These findings are according to study by Memon et al 17 , and Tariq et al 21 However, results are different from study of Gondivkar et al 22 showed more prevalence in graduates (32.0%).…”
Section: Discussioncontrasting
confidence: 73%
“…
In a recent study conducted by Tariq et al, (2020), majority of OSF patients consumed betel nut every day, average consumption being six packets per day for nine years (Tariq et al, 2020). Betel nut chewing
…”
mentioning
confidence: 99%
“…(World Health Organization, 2020). Several studies have established the association between tobacco, potentially malignant disorders and oral cancer stating that most oral cancers result from tobacco smoking or using tobacco in other forms (Awan and Patil, 2016;Gupta et al, 2017;Asthana et al, 2019;Mello et al, 2019;Tariq et al,…”
Section: Introductionmentioning
confidence: 99%